DETERMINANTS OF REPURCHASE INTENTIONS THROUGH CUSTOMER TRUST ON BRAND X’S WEBSITE - Jessica Sarah Amaris; Sanny Ekawati (Graduate Program of Universitas Tarumanagara, 2024)
This research was conducted to determine the direct and indirect influence of web design quality and service quality on repurchase intentions, through trust in brand X’s website in Jakarta. This study was conducted by distributing questionnaires. The sample used in this study was 100 respondents in Jakarta who had purchased products on the brand X’s website. This study used a non-probability sampling with purposive sampling techniques. Data is processed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) software. The result of this study shows that web design quality can affect trust, yet it cannot affect repurchase intentions directly. Furthermore, service quality can affect trust and repurchase intentions directly. Then trust can influence repurchase intentions. Web design quality can influence repurchase intentions indirectly through trust, however service quality cannot influence repurchase intentions through trust. The benefit of this research is to encourage e-commerce companies to pay more attention to their web design and service quality, as this can increase customers' desire to make repurchases.